PRAKTIK BAIK PENGGUNAAN DANA ALOKASI UMUM DI KECAMATAN PAYAKUMBUH SELATAN - Melga Amelia; Delfia Tanjung Sari (Halu Oleo University, 2024)
The The purpose of this study was to analyze the good practice of using the General Allocation Fund (DAU) in Payakumbuh Selatan Sub-district, Payakumbuh City. Data collection was conducted through semi-structured interviews. Data analysis was conducted using triangulation techniques, namely data reduction, data presentation, and conclusion drawing. The results of the study found that the realization of the use of DAU in the South Payakumbuh Sub-district showed very good performance, with a success rate of 95% in 2023. The process and all activities related to the use of DAU are carried out by the Budget User Authority (KPA), the Activity Technical Implementation Officer (PPTK), the Financial Administration Officer (PPK), the Treasurer, and several personnel who are assigned by each village. Employees in each kelurahan are assigned to succeed in the three focuses of the government through socialization related to stunting, technical guidance related to reducing inflation, and entrepreneurship training. There are several factors that inhibit the use of the DAU program, such as too high a comparison between the unit price listed in the Budget Implementation Document (DPA) and the real price in the field, the lack of personnel in several villages, and the existence of multiple positions that make the work process not optimal.